"Do No Harm": Fortifying MDT Collaboration in Changing Technological Times - KANE, BRIDGET THERESA; LUZ, SATURNINO (My University, 2013)
Purpose: To examine the changes in multidisciplinary medical team activity and practices, with respect to the amount of patient cases, the information needs and technology used, with up to 10 multidisciplinary teams (MDTs) in a large teaching hospital over a 10-year period. Methods: An investigation of MDT meeting activity was undertaken in November 2005 and repeated in November 2012 for the MDTs at a large university teaching hospital. Analysis of data from 8 MDTs was informed through long-term ethnographical study, and supplemented with 38 semi-structured interviews and a survey from 182 staff members of MDTs. Results: Work rhythms change over time as a function of the volume of work and technology changes, such as the use of a picture archive and communication system (PACS), videoconferencing and an electronic patient record (EPR). Maintaining cohesive teamwork, system dependability, and patient safety in the context of rapid change is challenging. Conclusions: Benefits of MDT work are in evidence, but the causes are not fully understood. Instead of asking `how can technology support more MDT activity??, we ask `how can we preserve the benefits of human?human interaction in an increasingly technological environment?? and `how can we ensure that we do no harm?? when introducing technology to support an increasingly demanding collaborative work setting. Introducing technology to streamline work might instead threaten the experienced improvement in patient services
PUBLISHED
Purpose: To examine the changes in multidisciplinary medical team activity and practices, with respect to the amount of patient cases, the information needs and technology used, with up to 10 multidisciplinary teams (MDTs) in a large teaching hospital over a 10-year period. Methods: An investigation of MDT meeting activity was undertaken in November 2005 and repeated in November 2012 for the MDTs at a large university teaching hospital. Analysis of data from 8 MDTs was informed through long-term ethnographical study, and supplemented with 38 semi-structured interviews and a survey from 182 staff members of MDTs. Results: Work rhythms change over time as a function of the volume of work and technology changes, such as the use of a picture archive and communication system (PACS), videoconferencing and an electronic patient record (EPR). Maintaining cohesive teamwork, system dependability, and patient safety in the context of rapid change is challenging. Conclusions: Benefits of MDT work are in evidence, but the causes are not fully understood. Instead of asking how can technology support more MDT activity? , we ask how can we preserve the benefits of human human interaction in an increasingly technological environment? and how can we ensure that we do no harm? when introducing technology to support an increasingly demanding collaborative work setting. Introducing technology to streamline work might instead threaten the experienced improvement in patient services.
Keywords: Collaborative Work; Teamwork; Medical Decision-Making